LinkedIn sebagai Media Alumni KPI UIN Raden Intan Lampung Membangun Identitas Profesional - Kms Iklasul Amal Ramadhan; Hasan Mukmin; Umi Rojiati (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
The advancement of digital technology has significantly changed communication patterns and career development through professional social media, particularly LinkedIn. This study aims to analyze the strategies of alumni of the Islamic Communication and Broadcasting Study Program (KPI), Faculty of Da'wah and Communication Sciences, UIN Raden Intan Lampung, in optimizing LinkedIn as a medium for career development and improving professional competence. Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation. The results showed that alumni implemented various strategies, including profile optimization, personal branding management, utilization of professional networks, and active engagement with educational content through accessing and sharing information. The intensity of use was grouped into three patterns: monthly passive use, weekly use, and active use two to four times per week focused on personal branding and networking. Differences in intensity of use affect the benefits obtained, including increased professional competence, network expansion, and increased access to career related information and opportunities.